An Analysis of Nonverbal Communication Used by the Resilient Heroine “Elodie” in the “Damsel” 2024 Film Directed by Juan Carlos Fresnadillo - Agustina, Eka; ul khusnah, anisa; rohmah, ainur (ENJEL: English Journal of Education and Literature, 2025)
This study aims to describe the nonverbal communication used by the resilient heroine “Elodie” in the film Damsel (2024) directed by Juan Carlos Fresnadillo. Used descriptive qualitative combined with content analysis to collecting the data from the Damsel (2024) film with a duration of 1 hour 48 minutes. The data collection technique in this study includes several steps: understanding the theory of nonverbal communication by DeVito, watching the film several times, reading the film script, identifying the nonverbal cues performed by Elodie, making notes and coding the data based on six categories. The aspects of nonverbal communication that are the focus of this study are body messages, facial communication, eye communication, touch communication, silence, and spatial messages and territoriality. Based on the results of data analysis, 55 nonverbal communication cues were found. The first finding is body messages with 4 data (7%), such as gestures and body movement. Second, facial communication with 10 data (18%), including expressions and smiles. Third, eye communication with 13 data (24%), like eye contact and eye avoidance. Fourth, touch communication with 12 data (22%), including emotional and ritual touches. Fifth, silence with 7 data (13%), referring to communicative pauses. And sixth, spatial messages and territoriality with 9 data (16%), such as proxemic distance. Thus, it can be concluded that the film Damsel contains many instances of nonverbal communication, and the most dominant aspect used by the character Elodie is facial communication with 13 occurrences or 24%.